2022
DOI: 10.3389/fphar.2022.835616
|View full text |Cite
|
Sign up to set email alerts
|

Ayurveda-based Botanicals as Therapeutic Adjuvants in Paclitaxel-induced Myelosuppression

Abstract: Chemotherapy-induced myelosuppression is one of the major challenges in cancer treatment. Ayurveda-based immunomodulatory botanicals Asparagus racemosus Willd (AR/Shatavari) and Withania somnifera (L.). Dunal (WS/Ashwagandha) have potential role to manage myelosuppression. We have developed a method to study the effects of AR and WS as therapeutic adjuvants to counter paclitaxel (PTX)-induced myelosuppression. Sixty female BALB/c mice were divided into six groups—vehicle control (VC), PTX alone, PTX with aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Shatavari administration to mice who were immunised against diphtheria, tetanus and pertussis resulted in a c. 16% greater antibody titre response at 14 days post-inoculation [ 42 ]. Administration of shatavari extract to mice with paclitaxel (PTX)-induced myelosuppression normalised leukocyte and neutrophil counts [ 43 ]. In recent years, several in silico studies have suggested that shatavari has the potential to inhibit COVID-19 via the hemagglutinin-acetylesterase (HE) glycoprotein receptor which is required for host infection [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Shatavari administration to mice who were immunised against diphtheria, tetanus and pertussis resulted in a c. 16% greater antibody titre response at 14 days post-inoculation [ 42 ]. Administration of shatavari extract to mice with paclitaxel (PTX)-induced myelosuppression normalised leukocyte and neutrophil counts [ 43 ]. In recent years, several in silico studies have suggested that shatavari has the potential to inhibit COVID-19 via the hemagglutinin-acetylesterase (HE) glycoprotein receptor which is required for host infection [ 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, paclitaxel can produce a variety of adverse responses or events, the most severe of which are allergic reactions. Allergic reactions to paclitaxel have been known to be fatal, and its harm to the blood system cannot be discounted ( Saggam et al, 2022 ). Apart from that, the primary emphasis of capecitabine and etoposide is on the circulatory system.…”
Section: Discussionmentioning
confidence: 99%
“…Shatavari administration to mice who were immunised against diphtheria, tetanus and pertussis resulted in a c. 16% greater antibody titre response at 14 days post-inoculation [42]. Administration of shatavari extract to mice with paclitaxel (PTX)-induced myelosuppression normalised leukocyte and neutrophil counts [43]. In recent years, several in silico studies have suggested that shatavari has the potential to inhibit COVID-19 via the hemagglutinin-acetylesterase (HE) glycoprotein receptor which is required for host infection [44][45][46].…”
Section: Discussionmentioning
confidence: 99%